Silibinin inhibits cytokine-induced STATs, MAPKs, NF-κB and AP-1 activation, and down-regulates HIF-1α and iNOS in human lung carcinoma A549 cells - Chittezhath, Manesh (2008)
Recently, we reported that silibinin inhibits primary lung tumor growth and progression in mice and down-regulates iNOS expression in tumors; however, the mechanisms of silibinin action are largely not understood. Also, the activation of signaling pathways inducing various transcription factors are associated with lung carcinogenesis and their inhibition could be an effective strategy to prevent and/or treat lung cancer. Herein, we used human lung epithelial carcinoma A549 cells to explore the potential mechanisms, and observed strong iNOS expression by cytokine mixture (CM, containing 100 U/ml IFN-γ + 0.5 ng/ml IL-1β + 10 ng/ml TNF-α). We also examined the CM-activated signaling cascades which could potentially up-regulate iNOS expression, and then examined the effect of silibinin (50-200 μM) on these signaling cascades. Silibinin treatment inhibited, albeit to different extent, the CM-induced activation of STAT1(Tyr-701), STAT3(Tyr-705), AP-1 family of transcription factors and NF-κB. The results for AP-1 were correlated with the decreased nuclear levels of phospho-c-Jun, c-Jun, Jun B, Jun D, phospho-c-Fos and c-Fos. Further, silibinin also strongly decreased CM-induced phosphorylation of ERK1/2, but only marginally affected JNK1/2 phosphorylation. Silibinin treatment also decreased constitutive p38 phosphorylation in the presence or absence of CM. Downstream of these pathways; silibinin strongly decreased CM-induced expression of HIF-1α, without any considerable effect on Akt activation. CM-induced iNOS expression was completely inhibited by silibinin. Overall, these results suggest that silibinin could target multiple cytokines-induced signaling pathways to down-regulate iNOS expression in lung cancer cells, and that could contribute to its overall cancer preventive efficacy against lung tumorigenesis.